Sonic Hedgehog dependent phosphorylation by CK1α and GRK2 is required for ciliary accumulation and activation of smoothened. - Yongbin Chen; Noriaki Sasai; Guoqiang Ma; Tao Yue; Jianhang Jia; James Briscoe; Jin Jiang (PLoS Biology)
Hedgehog (Hh) signaling regulates embryonic development and adult tissue homeostasis through the GPCR-like protein Smoothened (Smo), but how vertebrate Smo is activated remains poorly understood. In Drosophila, Hh dependent phosphorylation activates Smo. Whether this is also the case in vertebrates is unclear, owing to the marked sequence divergence between vertebrate and Drosophila Smo (dSmo) and the involvement of primary cilia in vertebrate Hh signaling. Here we demonstrate that mammalian Smo (mSmo) is activated through multi-site phosphorylation of its carboxyl-terminal tail by CK1α and GRK2. Phosphorylation of mSmo induces its active conformation and simultaneously promotes its ciliary accumulation. We demonstrate that graded Hh signals induce increasing levels of mSmo phosphorylation that fine-tune its ciliary localization, conformation, and activity. We show that mSmo phosphorylation is induced by its agonists and oncogenic mutations but is blocked by its antagonist cyclopamine, and efficient mSmo phosphorylation depends on the kinesin-II ciliary motor. Furthermore, we provide evidence that Hh signaling recruits CK1α to initiate mSmo phosphorylation, and phosphorylation further increases the binding of CK1α and GRK2 to mSmo, forming a positive feedback loop that amplifies and/or sustains mSmo phosphorylation. Hence, despite divergence in their primary sequences and their subcellular trafficking, mSmo and dSmo employ analogous mechanisms for their activation.